Comparison of Educational Thoughts of KH Abdurrahman Wahid and John Dewey on Humanist Education - Mufid, Ahmad; Asrori, Achmad; Safari , Safari (Journal Corner of Education, Linguistics, and Literature, 2024)
The essence of education is the process of humanizing humans through the formation of free and creative humans. However, data from various sources show that there is an increase in cases of violence among students and a lack of respect for human values. Therefore, a humanist educational approach is needed that is able to develop individual potential optimally and build social awareness to achieve a harmonious life. This study uses a library research method by reviewing various reference sources such as books, journals, articles, and previous research. The main literature used includes books by KH Abdurrahman Wahid on education and religious humanism as well as John Dewey's writings on pragmatism and experience-based education. Data are analyzed descriptively to identify similarities and differences in the thoughts of the two figures. The concept of humanist education developed by KH Abdurrahman Wahid and John Dewey provides an important contribution to understanding education as a means of humanizing humans. Gus Dur integrates religious values into education, while Dewey emphasizes experience-based education to form democratic and productive individuals. The combination of the thoughts of these two figures can be the basis for developing a more holistic and inclusive education system. In the Indonesian context, integrating this approach can help create an education system that is not only academically relevant, but also capable of building a tolerant, just, and prosperous national character.